2018
DOI: 10.11111/jkana.2018.24.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Career Plateau, Career Planning, Social Support, and Turnover Intention in Nurses

Abstract: Purpose: This study was a correlational research to examine the relationship between career plateau, career planning, social support and turnover intention experienced by nurses in the clinical nursing field. Methods: Participants were 237 nurses working in general hospitals with 100~300 beds located in G Metropolitan City. Data were collected from September 26 to October 6, 2016, and analyzed using the SPSS/WIN 22.0 program. Descriptive statistics, independent t-test, univariate ANOVA, Scheffé test, correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Third, the structural career plateau of student athletes had a positive effect on their career transition intention while their content career plateau had no effect on their career transition intention. This can be regarded as echoing the findings of preceding studies, which indicate that people move to another department or consider turnover (changing jobs) when they perceive a sense of structural plateau such that their promotion is suspended in their organization or their position has dropped [21], [24]. Therefore, student athletes look for another school or another team at a lower level, consider transferring to another school when they become a substitute player, and even give up their athletic career when entering a school of a higher grade.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Third, the structural career plateau of student athletes had a positive effect on their career transition intention while their content career plateau had no effect on their career transition intention. This can be regarded as echoing the findings of preceding studies, which indicate that people move to another department or consider turnover (changing jobs) when they perceive a sense of structural plateau such that their promotion is suspended in their organization or their position has dropped [21], [24]. Therefore, student athletes look for another school or another team at a lower level, consider transferring to another school when they become a substitute player, and even give up their athletic career when entering a school of a higher grade.…”
Section: Discussionsupporting
confidence: 81%
“…Second, the structural career plateau and content career plateau of student athletes had a negative effect on their exercise commitment. It has been reported that student athletes are frustrated with their reality and feel discouraged when they strongly perceive that they have reached a career plateau [21], and such perception of a career plateau affects their sense of stagnation in growth and leads to a sense of comparative deprivation [22], which prevents them from committing to their tasks [23]. It should be noted that preceding studies on student athletes are not enough so there is a limitation on the discussion targeting a nurse organization or a service organization, so careful examination is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies used a measurement that was developed by Gould (1979) for career planning (e.g. Renn, Steinbauer, Taylor, & Detwiler, 2014;Hirschi, Herrmann, & Keller, 2015;Spurk et al, 2015;Taber & Blankemeyer, 2015;Neureiter & Traut-Mattausch, 2017;Ko & Kim, 2018;Jawahar & Shabeer, 2019). The instrument consisted of six items, which scale aims to determine individuals' career aims and focusing on career development in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The unique role of NH RNs compared to acute-care-setting RNs can explain intention to stay. Emergency situations such as falls, suction, loss of consciousness, and difficulty breathing frequently occur in NHs [ 15 ]. Unlike acute care settings, however, physicians are not full-time, requiring RNs to make independent clinical judgments and decisions on emergency situations and administer first-aid to residents.…”
Section: Discussionmentioning
confidence: 99%
“…Most RNs are called in and expected to take emergency measures when a resident safety problem occurs at an NH [ 14 ]. NHs are prone to safety accidents due to most residents’ decreased cognitive and physical function [ 15 ]. RNs have difficulty performing their nursing duties due to the lack of safety culture; therefore, it is necessary to create a resident safety culture to cope with safety concerns [ 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%